Factors Influencing Consumer Purchase Intention Towards Beauty Products in Indonesia - Ida Ayu Dewi Komala Kartika; Adhi Prasetio (PT. Publikasiku Academic Solution, 2025)
This study employs a quantitative approach with purposive sampling of 100 Indonesian skincare users. Data were collected using questionnaires measuring variables including Celebrity Influencers’ Credibility and Attractiveness, Online Customer Reviews, Consumer Attitude, Brand Loyalty, Brand Awareness, e-WOM, Social Media Influencer, Perceived Quality, and Purchase Intention. Analysis was conducted using Structural Equation Modeling with the Partial Least Squares (PLS) method, suitable for smaller samples and complex variable relationships. Findings reveal that celebrity influencers’ credibility and attractiveness significantly enhance consumer attitudes toward promoted brands. Positive online customer reviews further strengthen these attitudes. Favorable consumer attitudes significantly boost brand loyalty, brand awareness, and e-WOM, which indirectly raise purchase intention. Consumer attitude also directly influences purchase intention, showing that positive perceptions encourage buying behavior. Additionally, the presence of social media influencers and perceived product quality significantly affect purchase intention, highlighting the role of external endorsements and quality perception in shaping purchasing decisions. These results underscore the strategic importance of leveraging credible influencers, fostering positive consumer attitudes, and maintaining product quality to drive purchase intentions in the competitive beauty industry.